2017
DOI: 10.1074/jbc.m116.753202
|View full text |Cite
|
Sign up to set email alerts
|

Src Acts as an Effector for Ku70-dependent Suppression of Apoptosis through Phosphorylation of Ku70 at Tyr-530

Abstract: Edited by Xiao-Fan WangSrc-family tyrosine kinases are widely expressed in many cell types and participate in a variety of signal transduction pathways. Despite the significance of Src in suppression of apoptosis, its mechanism remains poorly understood. Here we show that Src acts as an effector for Ku70-dependent suppression of apoptosis. Inhibition of endogenous Src activity promotes UV-induced apoptosis, which is impaired by Ku70 knockdown. Src phosphorylates Ku70 at Tyr-530, being close to the possible ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 89 publications
(133 reference statements)
0
17
0
Order By: Relevance
“…Besides, Src can phosphorylate caspase-8 at tyrosin 397 to suppress apoptosis ( Tsang et al, 2016 ). Src may also inhibit apoptosis via directly phosphorylation at tyrosin 530 of Ku-70, which is a crucial protein to repair DNA double-strand breaks ( Morii et al, 2017 ). These results suggest Src could activate several pathways to cause chemoresistance in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Src can phosphorylate caspase-8 at tyrosin 397 to suppress apoptosis ( Tsang et al, 2016 ). Src may also inhibit apoptosis via directly phosphorylation at tyrosin 530 of Ku-70, which is a crucial protein to repair DNA double-strand breaks ( Morii et al, 2017 ). These results suggest Src could activate several pathways to cause chemoresistance in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although Src substrates have been extensively hunted so far 5 , 6 , 28 , we showed that Src-family members are localized to the nucleus besides the plasma membrane 29 – 31 and revealed novel roles for Src-mediated tyrosine phosphorylation of chromosome-associated proteins 32 34 . Given that chromosome abnormalities happen until 24 h after v-Src induction (Figs 4 , 6 , 7 ), we hypothesize that some chromosome-associated proteins that are normally away from tyrosine phosphorylation may be aberrantly phosphorylated by v-Src in this period.…”
Section: Discussionmentioning
confidence: 87%
“…Cell lysates were prepared in SDS-sample buffer were separated by SDS-PAGE and electrotransferred onto polyvinylidene difluoride membranes (PVDF, Millipore). Immunodetection was performed as reported previously 20 , 34 , 36 , 43 . Sequential reprobing of membranes with a variety of antibodies was performed after the complete removal of primary and secondary antibodies from membranes in stripping buffer or inactivation of horseradish peroxidase by 0.1% NaN 3 , according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…1 a). Even though a number of anti-Fyn antibody reagents were commercially available to us, it was not possible to visualize endogenous centrosomal Fyn in HeLa cells despite their proper protein expression of Fyn 19 , 28 . To investigate the centrosomal localization of endogenous c-Src, we used Caco-2 cells, which strongly express c-Src, and found that c-Src also accumulated in the centrosome region (Fig.…”
Section: Resultsmentioning
confidence: 99%